RADIATION-HYGIENIC JUSTIFICATION OF OUTPATIENT RADIONUCLIDE THERAPY - B. Ja. Narkevich; S. V. Shiryaev; A. N. Klyopov; N. N. Lipanova; Yu. V. Lysak (Радиационная гигиена)
The possibility of the use of the different therapeutic radiopharmaceuticals labeled with one of the 19 β-γ-emitting radionuclides or 6 α-β-γ-emitting radionuclides in the outpatient regime was identified in the estimateinvestigations. A criterion for admissibility of outpatient regime is effective dose of individuals from the population who occasionally or permanently contact the patients after the radiopharmaceutical introduction. Basing on the dose limits established by the Radiation Safety Standard-99/2009, maximal allowable activities of the mentioned radionuclides were calculated for various geometries and exposure scenarios. It is shown that only patients taking radionuclide therapy courses with 111In and 131I have to be hospitalized even in the case of the most conservative exposure conditions.